Nanostructured polyelectrolyte complexes based on chitosan and sodium alginate containing rifampicin for the potential treatment of tuberculosis. (2nd December 2021) - Turco, Bruna Ortolani; Boni, Fernanda Isadora; Gremião, Maria Palmira Daflon; Chorilli, Marlus
Abstract: Nanostructured polyelectrolyte complexes (nano PECs) were obtained by polyelectrolyte complexation technique from chitosan (CS) and sodium alginate (SA). Different polymer proportions were tested, as well as the addition order and homogenization type, to assess the influence on the nano PECs characteristics. The spherical shape and nanometric scale of the systems were observed by scanning electron microscopy (SEM). Nano PECs size, PDI, and zeta potential (ZP) ranged from 252 to 616 nm, from 0.22 to 0.73 and −50 to 30 mV, respectively. The increase of polymer proportion and the ultra-turrax homogenization led to the enlargement of particles size and PDI. However, no influence was observed on the ZP. The NP1s-Rb and NP4s-Rb, obtained through the sonicator with rifampicin (RIF) added before the CS and SA complexation, were selected due to the most promising characteristics of diameter (301 and 402 nm), PDI (0.27 and 0.26), and RIF incorporation (78 and 69%). The release profiles of RIF incorporated in both nano PECs were similar, with a sustained release of the drug for 180 min in phosphate buffer pH 7.2. The Weibull and the Korsmeyer–Peppas models better describe the RIF release from NP1s-Rb and NP4s-Rb, respectively, demonstrating that the release process was driven by different mechanism according to the particle composition. The nano PECs were lyophilized to prolong it stability and for possible nebulization. The addition of dextrose to the system allowed for resuspension after lyophilization. Therefore, with the results obtained, the incorporation of RIF in nano PECs based on CS and SA presents a promising system for the treatment of tuberculosis.